2019
DOI: 10.1109/access.2019.2936828
|View full text |Cite
|
Sign up to set email alerts
|

An Improved ELM Model Based on CEEMD-LZC and Manifold Learning for Short-Term Wind Power Prediction

Abstract: The nonlinear characteristics of wind power series and random fluctuation characteristics of wind resources have a harmful effect on stability of wind power prediction. This paper proposes a novel hybrid wind power short-term prediction model for improving precision and stability of wind power prediction. Firstly, the non-stationary wind power time series is decomposed by complete ensemble empirical mode decomposition-Lempel-Ziv complexity (CEEMD-LZC). Secondly, local linear embedding (LLE) is used to reduce t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…First, determine the K value of the least square fitting. By testing the K value in References [10,20], the optimal K = 15 can be achieved. Then, normalize and matrix the fitted data with BN.…”
Section: Select Combination Weighting Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, determine the K value of the least square fitting. By testing the K value in References [10,20], the optimal K = 15 can be achieved. Then, normalize and matrix the fitted data with BN.…”
Section: Select Combination Weighting Methodsmentioning
confidence: 99%
“…Even though the above research can meet the basic goal of wind power prediction, it is still easy to fall into the limitations of the model itself, which can be supplemented by the optimization algorithm or other models to further improve the prediction effect. Therefore, the method of multi model combination was introduced to overcome the limitations of the single model [14][15][16][17][18][19][20][21]. The work in Reference [14] proposed a combination model of the support vector regression model and grey model, and the result showed that the combination model can improve the prediction accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the power imbalance of the wind turbines can result in a significant loss in their economical profit. Accurately predicting wind power is essential to decrease the impact of uncertainty and energy costs and enabling good management and integration of wind turbines in a smart grid [1]- [4].…”
Section: Introductionmentioning
confidence: 99%
“…But when it comes to short-term wind power prediction, large calculation consumption makes the physical model not competent for high-precision prediction. And the statistical model such as Auto-Regressive and Moving Average model (ARMA) [5], Autoregressive Integrated Moving Average model (ARIMA) [6], Support Vector Machine (SVM) [7], Least Square Support Vector Machine (LSSVM) [8], Extreme Learning Machine (ELM) [9]- [11] are adopted because of its fast calculation speed and high accuracy. The hybrid model not only uses the statistical model but also integrates the physical model, especially using NWP.…”
Section: Introductionmentioning
confidence: 99%